If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(4a + 3) + -5(2 + -1a) = 3(2a + 3) + -7 Reorder the terms: -2(3 + 4a) + -5(2 + -1a) = 3(2a + 3) + -7 (3 * -2 + 4a * -2) + -5(2 + -1a) = 3(2a + 3) + -7 (-6 + -8a) + -5(2 + -1a) = 3(2a + 3) + -7 -6 + -8a + (2 * -5 + -1a * -5) = 3(2a + 3) + -7 -6 + -8a + (-10 + 5a) = 3(2a + 3) + -7 Reorder the terms: -6 + -10 + -8a + 5a = 3(2a + 3) + -7 Combine like terms: -6 + -10 = -16 -16 + -8a + 5a = 3(2a + 3) + -7 Combine like terms: -8a + 5a = -3a -16 + -3a = 3(2a + 3) + -7 Reorder the terms: -16 + -3a = 3(3 + 2a) + -7 -16 + -3a = (3 * 3 + 2a * 3) + -7 -16 + -3a = (9 + 6a) + -7 Reorder the terms: -16 + -3a = 9 + -7 + 6a Combine like terms: 9 + -7 = 2 -16 + -3a = 2 + 6a Solving -16 + -3a = 2 + 6a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-6a' to each side of the equation. -16 + -3a + -6a = 2 + 6a + -6a Combine like terms: -3a + -6a = -9a -16 + -9a = 2 + 6a + -6a Combine like terms: 6a + -6a = 0 -16 + -9a = 2 + 0 -16 + -9a = 2 Add '16' to each side of the equation. -16 + 16 + -9a = 2 + 16 Combine like terms: -16 + 16 = 0 0 + -9a = 2 + 16 -9a = 2 + 16 Combine like terms: 2 + 16 = 18 -9a = 18 Divide each side by '-9'. a = -2 Simplifying a = -2
| 7x=-6x+9 | | 3m+4.5m=15 | | 4x-8-x=22 | | 3.5=17s-5s | | -7(4x-7)=105 | | 0.11p+1.5=2.49 | | 1.12+1.125y=8.62 | | -x-9+7x=21 | | 0.25m+0.1m=9.8 | | -(z+5)=-14 | | 5x+6= | | 5(4+p)=3(3p-1)-9 | | m(2)+4(15.5)=m+4(3) | | 5x-7=0 | | 0.5(x-12)=4 | | 5n+10=5 | | 29=a+5 | | 8(3x+1)=-80 | | -2=-(2-8) | | 2m+40=3m | | 4x+3.6+x=1.2 | | -6x-7=-3-8x | | 5v-3-4v=13 | | -6(5x+2)=198 | | -6(5x+2)=197 | | 5n+2n-(3-10n)= | | x-8=2x+3 | | 5(2+y)=7 | | 8(3x+1)=28 | | 48=8(x+2) | | 434=-31y | | m+5(m-1)=7 |